2003
DOI: 10.1097/00004770-200303000-00007
|View full text |Cite
|
Sign up to set email alerts
|

Shearing Bond Strength of Endodontic Sealers to Gutta-percha

Abstract: Strength of the bond of root canal sealers to gutta-percha seems to be an important property for maintaining the integrity of the apical seal. In the few studies published, different models and assessment methods were used. The purpose of our study was to adapt an effective and easily reproducible model and to test it on nine contemporary commercially available endodontic sealers. Gutta-percha disks with a diameter of 10 mm and thickness of 2 mm were prepared by warming gutta-percha cones and then fixed with p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
28
0
7

Year Published

2003
2003
2012
2012

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(41 citation statements)
references
References 9 publications
4
28
0
7
Order By: Relevance
“…Their popularity has been due, in part, to the fact that they contain no eugenol, which inhibits the polymerization of resins (143) and can interfere with bonding (97,102). Low bond strengths are reported for the epoxy resin sealers to gutta-percha (165,166) and to dentin (6 MPa or less) (158,(165)(166)(167)(168). Use of a dentin bonding agent improved bond strength of AH-26 (167,169) but no improvement was shown in a study with AH Plus and Thermafil (170).…”
Section: Current Resin and Glass-ionomer Obturating Materials Ah 26 Amentioning
confidence: 99%
“…Their popularity has been due, in part, to the fact that they contain no eugenol, which inhibits the polymerization of resins (143) and can interfere with bonding (97,102). Low bond strengths are reported for the epoxy resin sealers to gutta-percha (165,166) and to dentin (6 MPa or less) (158,(165)(166)(167)(168). Use of a dentin bonding agent improved bond strength of AH-26 (167,169) but no improvement was shown in a study with AH Plus and Thermafil (170).…”
Section: Current Resin and Glass-ionomer Obturating Materials Ah 26 Amentioning
confidence: 99%
“…It was noted that AH 26 has a very good adhesion capability to dentin, as well as to gutta-percha (18-20). It has also been found that this effective adhesiveness capability does not change with heat application (21,22) , and that when used with gutta-percha, it increases resistance to vertical fracture (17,21).…”
Section: Introductionmentioning
confidence: 99%
“…Durante o preparo biomecânico do sistema de canais radiculares, a remoção da dentina para promover a limpeza e desinfecção, bem como modelar o canal para receber a obturação, resulta no enfraquecimento radicular (REEH et al, 1989;NEWMAN et al, 2003;MORGANO et al, 2004;TAIT et al, 2005;DIETSCHI et al, 2007). Além disso, em um dente desvitalizado há diminuição de 13,2% na umidade da dentina coronária e perda de umidade na dentina radicular ainda maior, fazendo com que sua capacidade de deformação elástica seja alterada, podendo resultar em fratura, o que interfere no sucesso do tratamento (SCHWARTZ; ROBBINS, 2004;BONFANTE et al, 2007;ZOGHEIB et al, 2008).…”
Section: Análise Da Interface Dentina/adesivo/resina Por Mev: Avaliaçunclassified
“…Além da camada de smear, há ainda outros fatores que dificultam ou mesmo impedem o processo de hibridização, como as diferentes concentrações de túbulos dentinários por região da raiz, o volume de água presente e a disposição conjunta de materiais de natureza diferente em um mesmo ambiente (CARRIGAN et al, 1984;NAKABAYASHI et al, 1991;DE DEUS et al, 2002;MANNOCCI et al, 2004). Em relação a este último, há evidências que indicam que há influência direta entre os resíduos dos cimentos endodônticos presentes nos túbulos dentinários e os teste de cisalhamento por extrusão (push-out), com velocidade de cruzeta de 0,5 mm/min (MENDOZA et al, 1997;SCHWARTZ et al, 1998;FRANCO et al, 2002;TAGGER et al, 2003;ALFREDO et al, 2006;HAYASHI et al, 2006;MACCARI et al, 2007;PUTIGNANO et al, 2007;DIAS et al, 2009), seguida da análise da interface adesiva em microscopia eletrônica de varredura. As falhas que ocorreram após o teste de push-out foram analisadas e categorizadas como adesivas, coesivas ou mistas, conforme preconizado por SALEH et al (2003).…”
Section: Análise Da Interface Dentina/adesivo/resina Por Mev: Avaliaçunclassified
See 1 more Smart Citation